Policing Women's Bodies: Pregnancy, Embodiment, and Gender Relations in Canadian Police Work. (October 2019) - Langan, Debra; Sanders, Carrie B.; Gouweloos, Julie
Despite the influx of women in policing, women continue to face barriers to their full inclusion. In this article, we put women's bodies at the center of our analysis by theorizing how pregnancy shapes the gendered interactions and experiences of women police at work. Through in-depth, qualitative interviews with 52 Canadian officers, we find that pregnancy frames women's bodies "out of order" for "police work" and positions women even further from the ideal police body, which is ostensibly male. In response, women engage in myriad strategies to reassert their value as officers, strategies that require women to do additional labor.